TRANSLATIONAL STUDY OF GUNSHOT INJURY TO THE COLON BY MODERN TYPES OF BULLETS - Tsymbaliuk V.І.; Lurin, I.A.; Gumeniuk, K.V.; Savitsky, O.F.; Popova, O.M.; Gorobeiko, M.B.; Dinets, A.V. (World of Medicine and Biology, 2022)
Gunshot injuries to the colon are frequent in combat casualties, including the current invasion of Russia into Ukraine. Colon wounds are associated with high mortality and severe purulent-septic complications. In this translational study, we investigated gunshot wounds to the colon in 374 servicemen who were injured in East Ukraine. In the experimental part, a special certified ballistic gel 10 % FBI Ballistic Block was used for ballistic analyses of various bullets to confirm clinical data. Data analyses showed that the severity of colon injuries depended on the type of wounding projectile, which was confirmed in gel experiments. The action of the wounding projectile bullet “V-Max” 5.45x39 mm (with expansive properties) showed significant differences in relation to the colon injury as compared to the usual all-shell claw “PS” (p